Automated Extracellular Volume Fraction Mapping Provides Insights Into the Pathophysiology of Left Ventricular Remodeling Post–Reperfused ST‐Elevation Myocardial Infarction. Issue 7 (July 2016) - Bulluck, Heerajnarain; Rosmini, Stefania; Abdel‐Gadir, Amna; White, Steven K.; Bhuva, Anish N.; Treibel, Thomas A.; Fontana, Marianna; Gonzalez‐Lopez, Esther; Reant, Patricia; Ramlall, Manish; Hamarneh, Ashraf; Sirker, Alex; et al.
Abstract : Background: Whether the remote myocardium of reperfused ST‐segment elevation myocardial infarction (STEMI) patients plays a part in adverse left ventricular (LV) remodeling remains unclear. We aimed to use automated extracellular volume fraction (ECV) mapping to investigate whether changes in the ECV of the remote (ECVR emote ) and infarcted myocardium (ECVI nfarct ) impacted LV remodeling. Methods and Results: Forty‐eight of 50 prospectively recruited reperfused STEMI patients completed a cardiovascular magnetic resonance at 4±2 days and 40 had a follow‐up scan at 5±2 months. Twenty healthy volunteers served as controls. Mean segmental values for native T1, T2, and ECV were obtained. Adverse LV remodeling was defined as ≥20% increase in LV end‐diastolic volume. ECVR emote was higher on the acute scan when compared to control (27.9±2.1% vs 26.4±2.1%; P =0.01). Eight patients developed adverse LV remodeling and had higher ECVR emote acutely (29.5±1.4% vs 27.4±2.0%; P =0.01) and remained higher at follow‐up (28.6±1.5% vs 26.6±2.1%; P =0.02) compared to those without. Patients with a higher ECVR emote and a lower myocardial salvage index (MSI) acutely were significantly associated with adverse LV remodeling, independent of T1Remote, T1Core and microvascular obstruction, whereas a higher ECVI nfarct was significantly associated with worse wall motion recovery. Conclusions: ECVR emote was increased acutely in reperfused STEMI patients. Those with adverse LV remodeling had higher ECVR emote acutely, and this remained higher at follow‐up than those without adverse LV remodeling. A higher ECVR emote and a lower MSI acutely were significantly associated with adverse LV remodeling whereas segments with higher ECVI nfarct were less likely to recover wall motion.